AGRO-ECOLOGICAL AND SOCIO-ECONOMIC ASPECTS OF CROP PROTECTION IN CHILI-BASED AGRIBUSINESS IN CENTRAL JAVA - Joko Mariyono (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2017)
The purpose of this study is to analyze the socio-economic and agro-ecological aspects of chili production in three selected communities of three districts —Magelang, Brebes, and Rembang—that represent distinct agro-ecosystems of chili cultivation within Central Java province. This is to answer a problem statement that chili farming still faces crop protection aspects as limiting factors in chili production. This study uses quantitative descriptive methods. Data were compiled from a survey of 160 chili farmers in 2010-2011. The results show that yield loss due to pests and diseases was considerable, and some of these problems were becoming difficult to control. The three top pests were thrips, mites, and whitefly; and the top three diseases were Anthracnose, Gemini-viruses, and Phytophthora. During the wet season, risk of anthracnose was very high; in the dry season, risk of yield lost to Gemini-viruses and Phytophthora was high. The potential losses could reach 100%. There is a crucial need to solve the problems by enhancing farmers’ knowledge and involving research institutions focusing on crop protection strategy.